1998
DOI: 10.2169/internalmedicine.37.1009
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Nasal Continuous Positive Airway Pressure on 24-Hour Blood Pressure and Catecholamines in Patients with Obstructive Sleep Apnea.

Abstract: To assess the acute effects of nasal continuous positive airway pressure (CPAP) on the 24-hour blood pressure and the secretion of catecholamines in urine and plasma, we investigated the changes in the 24-hour blood pressure and urinary and plasma concentrations of epinephrine (E) and norepinephrine (NE) in 26 men with obstructive sleep apnea (OSA) with and without nasal CPAP. Nasal CPAPresulted in significant decreases in the daytime diastolic pressure (from 86 ± 16 mmHgto 83 ± 12 mmHg), the nighttime diastol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 24 publications
3
52
1
1
Order By: Relevance
“…These findings mirror those of Minemura et al, 31 whose uncontrolled study demonstrated nighttime and daytime reductions in diastolic BP but only nighttime reduction in systolic BP with CPAP therapy. Some have suggested that OSA may predispose to both systolic and diastolic hypertension at night, but initially, 73 or primarily, 74 diastolic hypertension during the day.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These findings mirror those of Minemura et al, 31 whose uncontrolled study demonstrated nighttime and daytime reductions in diastolic BP but only nighttime reduction in systolic BP with CPAP therapy. Some have suggested that OSA may predispose to both systolic and diastolic hypertension at night, but initially, 73 or primarily, 74 diastolic hypertension during the day.…”
Section: Discussionsupporting
confidence: 88%
“…10,39 -49 Some studies found a reduction only in nocturnal 41,50 or in daytime BP 44 with continuous positive airway pressure (CPAP) therapy. Several showed a decrease in both nocturnal and daytime BP with CPAP therapy, 10,31,[43][44][45][46]49,51,52 whereas other studies demonstrated no BP change. 40,48,53,54 Several limitations exist in many of the prior studies that examined the effects of OSA treatment on BP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have reported a reduction of plasma and/or urinary NE and systemic blood pressure as early as the first night on CPAP [28,29]. Recent controlled studies demonstrated that nasal CPAP therapy for 4-9 weeks reduced blood pressure by 1-10 mmHg [4][5][6][7], in that the degree of blood pressure reduction appeared to be dependent on the severity of established hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,11 Moreover, this altered sympathetic activity has been demonstrated to be corrected by continuous positive airway pressure treatment. 12,13 The aim of the present study is to estimate the prevalence of hypertension in patients with sleep-disordered breathing (SDB) in an Indian population, estimate the sympathetic activity in these patients as assessed by blood catecholamine levels, and assess the correlation between the catecholamine levels and BP in these patients.…”
Section: Introductionmentioning
confidence: 99%